Needs Assessment of Anatomy for the Gastroenterology Masters Course among Teachers, Practitioners and Students: Coverage of Topics other than Topographic Anatomy (Bangladesh Journal of Anatomy, 2014)
Context: Absence of formally specified course content and objectives, instructional methodology, and assessment system for Anatomy in the MD Gastroenterology course of Bangladesh has led to confusion in the implementation of its residency curriculum with respect to Anatomy. Needs assessment of Anatomy for the would-be gastroenterologists among the stakeholders of the course would help solving this problem. This study aimed at having feedback on the coverage of topics of Anatomy other than topographic anatomy in teaching and assessment of the MD Gastroenterology course attended by them. Materials & Methods: A Cross-Sectional study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from July 2002 to December 2003. A questionnaire (based on analysis of a textbook of Gastroenterology) with close-ended questions was sent to nine teachers/practitioners, students (residents) and thesis part students of the MD Gastroenterology course. Results: The number of topics that were felt to covered as required by majority of the participants was 2 out of 11. For the most of the topics, teaching or assessment was felt to be more than required. Though more than 70% respondents considered the course as customized and 75% tended to agree that teaching and assessment had been useful in clinical work, 55.6% thought that it had catered more recall-level knowledge, 85% did not think that a problem-based approach had been taken in the course. Conclusion: Considering the findings of this study positive steps can be taken to reorganize of Anatomyportion of the course and making it clinically to the gastroenterologists. DOI: http://dx.doi.org/10.3329/bja.v11i2.20672 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 62-67